Critical Strategies for Academic Thinking and Writing - Kiniry, Malcolm and Rose, Mike. (Boston Bedford Books of St. Martins Press, 1993)
Our aim in Critical Strategies is to help you, as a writer, to think and write responsively and flexibly in academic situations. By writing responsively, we mean in thoughtfully close relation to what youve been asked to read or hear or observe. By writing flexibly, we mean with confident awareness of the many choices open to you. By academic situations, we mean the many opportunities youll have in college to reconstruct what youve learned and to articulate what you think about it.
Keywords: Writing